Focused ultrasound therapy in movement disorders: management roadmap toward optimal pathway organization - Rinaldo, Sara; Cilia, Roberto; Leta, Valentina; Gammone, Mariarosaria; Andreasi, Nico Golfrè; Colucci, Fabiana; Braccia, Arianna; Telese, Roberta; Poli, Marco Fusar; Levi, Vincenzo; Romito, Luigi Michele Antonio; Ghilemetti, Francesco; et al. (Frontiers in Neurology, 2024)
MRI-guided focused ultrasound (MRgFUS) lesioning is an innovative, safe and effective treatment which provides an innovative development in the field of minimally invasive stereotactic neurosurgery. Based on the application of focused ultrasound energy under full MR planning and thermal imaging control, unilateral lesioning of the thalamus, subthalamic nucleus, and globus pallidus is indicated for the treatment of movement disorders, including essential tremor, Parkinson's disease, and dystonia.We started to apply this technique in February 2019 for the treatment of patients with movement disorders. The authors developed a diagnostic therapeutic care pathway, which is herewith proposed and applied as an explication of standard clinical practice in use. The project was the result of the application of different methods such as Health Technology Assessment (HTA), Strengths, Weaknesses, Opportunities and Threats analysis (SWOT) and Demin -Plan, Do, Check, Act (PDCA) cycle.The aim of this project was to standardize the MRgFUS diagnostic-therapeutic pathway (DTP), describe its application and the appropriateness of different phases (patient selection, intervention phase and follow-up). Here, we described in detail our experience in the DTP application from 2019 up to now in 610 patients with movement disorders.